Political Internet Memes in Indonesia: Insulting the President in the 2019 Presidential Election Adi Bayu - MAHADIAN, ADI BAYU; Hashim, Rohani (Journal of Contemporary Issues in Media & Communication (JCIMC), 2022)
This article analyses the discourse of internet memes 'Jokowi planga-plongo' that mocked and insulted the President in the 2019 Indonesian presidential election. These insults and mockery toward the president were severe that it urged the government to issue an article regarding the insult to the president and his vice. We collected 'Jokowi planga-plongo' memes during the 2019 presidential election campaign. We analyse qualitatively with the social semiotics analysis assisted by the internet meme theory and bisociation theory. We found that Indonesians use abusive and non-abusive memes to insult the President. The non-abusive insulting memes created without a harsh and abusive words can sneak from the EIT law. Besides, it was also found that the non-abusive memes are more in quantity than the abusive ones to avoid the law violation.